STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN MUTU PENDIDIKAN DI MTS ASSHULTHON KADEMANGAN PROBOLINGGO - Nisail Fitriah, Khoirotun (As-Sulthan Journal of Education, 2024)
This type of research uses qualitative methods with a descriptive pattern case study approach. This study also uses the theoretical framework of leadership strategies, theory of headmaster, and the theory of quality of education. This study came to the findings that 1) The headmaster leadership strategy in Islamic Junior High School of Assulthon Kademangan Probolinggo is quite significant in improving the quality of education in Islamic Junior High School of Assulthon Kademangan Probolinggo, especially in its strategy as a mediator and inspiratory with all its limitations and advantages. The affection and psychomotor aspects of headmaster leadership in Islamic Junior High School of Assulthon Kademangan Probolinggo can be used as a pilot for how to become a headmaster who plays an active role in the quality of education quality. 2) The quality of education in Islamic Junior High School of Assulthon Kademangan Probolinggo is not yet fully qualified, but it has an optimization on the creativity of educators in carrying out the learning process, the leadership of headmaster who is persuasive to protect and support related parties, which certainly encourages the improvement of the quality of education. 3) Constraints faced in taking the strategy of the madrasah head in improving the quality of education in Islamic Junior High School of Assulthon Kademangan Probolinggo include internal and external constraints that are possible to be overcome as optimizing the headmaster’s strategy in improving the quality of his education